2023
DOI: 10.1136/bmjopen-2023-073592
|View full text |Cite
|
Sign up to set email alerts
|

Association between leisure sedentary behaviour and uterine fibroids in non-menopausal women: a population-based study

Yunrui Sun,
Xiaoyu Han,
Zhongxin Hou
et al.

Abstract: ObjectiveSedentary behaviour is associated with a variety of adverse health outcomes, including obesity, oestrogen metabolism and chronic inflammation, all of which are related to the pathogenesis of uterine fibroids (UFs). This study aimed to explore the relationship between leisure sedentary time (LST) and UFs.DesignCross-sectional.SettingWe conducted a cross-sectional analysis of data from patients from the Yunnan region in the China Multi-Ethnic Cohort Study.ParticipantsA total of 6623 non-menopausal women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…The hypothesis that a high BMI contributes to an increased risk of UFs was supported by our study, specifically indicating a higher risk in premenopausal women [ 27 , 28 ]. Baird et al found that women who engaged in at least four hours of vigorous physical activity per week were more likely to experience a decreased risk of UFs [ 29 ].…”
Section: Lifestyle Interventionssupporting
confidence: 75%
“…The hypothesis that a high BMI contributes to an increased risk of UFs was supported by our study, specifically indicating a higher risk in premenopausal women [ 27 , 28 ]. Baird et al found that women who engaged in at least four hours of vigorous physical activity per week were more likely to experience a decreased risk of UFs [ 29 ].…”
Section: Lifestyle Interventionssupporting
confidence: 75%